Risk of Congestive Heart Failure in Early Breast Cancer Patients Undergoing Adjuvant Treatment With Trastuzumab: A Meta-Analysis - Long, Hui-Dong (Oncologist, 2016)
BACKGROUND. The use of trastuzumab has proven to be a successful strategy in patients with human epidermal growth factor receptor 2 (HER2)-positive breast cancer; however, it is associated with an increased risk of cardiac dysfunction. We performed an up-to-date, comprehensive meta-analysis to clarify the risk of congestive heart failure (CHF) in patients with early breast cancer receiving different durations of adjuvant trastuzumab with the longest-term follow-up. METHODS. Eligible studies included randomized control trials of HER2-positive early breast cancer patients with or without trastuzumab in adjuvant chemotherapy. Adequate reporting of CHF data were required for inclusion. Statistical analyses were conducted to calculate the overall incidence, relative risk (RR), and 95% confidence interval (CI) by use of a fixed-effects model. RESULTS. Six randomized control trials including 18,111 patients were identified. The overall incidence of high-grade CHF in patients treated with trastuzumab versus placebo was 1.44% (95% CI, 0.79%–2.64%) and the RR was 3.19 (95% CI, 2.03–5.02; p < .00001). In subgroup analysis, the difference in CHF incidence failed to achieve significance. The RR for 8 mg/kg trastuzumab (high dose) was greater than that for 4 mg/kg (low dose) (RR, 6.79, 95% CI, 2.03–22.72, p = .0001; versus RR, 2.64; 95% CI, 1.61–4.32; p = .002). Additionally, higher RRs were observed for patients receiving trastuzumab for 1 year (RR, 3.29; 95% CI, 2.07–5.25) and 2 years (RR, 9.54; 95%CI, 2.19–41.43), but not 9 weeks (RR, 0.50; 95% CI, 0.05–5.49) compared with control groups. No evidence of publication bias was observed. CONCLUSION. Adjuvant trastuzumab therapy was strongly associated with an increased risk of significant CHF in patients with early breast cancer, particularly in 2-year use. IMPLICATIONS FOR PRACTICE: This comprehensive meta-analysis evaluated the risk of congestive heart failure with a usage profile of adjuvant trastuzumab in patients with early breast cancer. Before initiating treatment with trastuzumab, a risk-benefit analysis for individual patients should be critically evaluated, considering that the prognosis is closely related to drug dose and duration of use. Cardiac function should be monitored throughout the treatment period and also during follow-up. Thus, early identification of trastuzumab-related cardiac dysfunction can allow effective medical intervention, elimination of symptoms, recovery of function, and continuation of trastuzumab therapy.